Application of waste cooking oil (WCO) biodiesel in a compression ignition engine. (15th July 2016) - Hwang, Joonsik; Bae, Choongsik; Gupta, Tarun
Highlights: The WCO biodiesel had longer injection delay than diesel. The WCO biodiesel showed lower equivalence ratio along the spray than diesel. The WCO biodiesel was advantageous in reduction of CO, HC and smoke emissions. The WCO biodiesel showed lower level of flame luminosity than diesel. Abstract: The comprehensive spray and combustion characteristics of waste cooking oil (WCO) biodiesel (B100) and conventional diesel fuels were investigated. The injection rate was measured by Bosch method and spray test was performed in a constant volume chamber under non-evaporating condition. The fuels were injected at injection pressures of 80 and 160 MPa with injection durations of 625 and 410 μs, respectively. From the injection rate experiment, the WCO biodiesel exhibited relatively longer injection delay than diesel due to higher viscosity. The WCO biodiesel also showed longer liquid tip penetration length and narrower spray angle regardless of fuel injection pressure. Nevertheless, the calculated equivalence ratio along the axial direction of spray proved that WCO biodiesel had lean fuel–air ratio compared to diesel due to inherent oxygen content in the fuel molecule. A series of engine experiments was performed to investigate the combustion and emission characteristics in an optically accessible compression ignition engine equipped with a common-rail system. The net indicated mean effective pressures (IMEPnet ) of 0.16–0.93 MPa were tested under an engine speed of 1400 r/min. The fuel injection timing was modified from 60 to 0 crank angle degree (CAD) before top dead center (bTDC) by 5 CAD. The WCO biodiesel had a slightly lower peak of in-cylinder pressure and fuel efficiency than diesel due to lower heating value. In terms of emissions, the WCO biodiesel had benefits in reduction of carbon monoxide, unburned hydrocarbon and smoke emissions in conventional diesel operating condition. On the other hand, however, the emission characteristics were deteriorated as the injection timing was advanced and the engine load was increased. The combustion imaging showed that the WCO biodiesel had lower flame luminosity and shorter visible flame duration than diesel.